PHYSICAL THERAPY OF MIDDLE-AGED PEOPLE WITH COXARTHROSIS IN THE OUTPATIENT STAGE OF REHABILITATION (Physical Culture and Sport: Scientific Perspective, 2024)
Physical therapy plays a key role in reducing the symptoms of coxarthrosis and improving the functional state of patients. The outpatient stage of rehabilitation is critical, since it is during this period that patients are often left without proper support, which can lead to ineffective recovery. Purpose of the study: to theoretically substantiate the features of physical therapy for middle-aged people with coxarthrosis at the outpatient stage of rehabilitation. Research methods. The work used theoretical research methods: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodological literature. Results of the work. Physical therapy is an important component of the rehabilitation process for middle-aged people with coxarthrosis, as it helps reduce pain, improve the functional activity of joints and improve the overall quality of life of patients. Properly selected physical exercises aimed at strengthening the muscles around the hip joint, increasing the amplitude of joint movement, allow you to reduce the load on the joint and improve its function. Taking into account age characteristics and individual needs of middle-aged patients is an important aspect of successful rehabilitation. Individually selected physical therapy programs, including exercises to improve joint stability, increase flexibility and strengthen muscles, allow you to effectively cope with the symptoms of coxarthrosis and reduce the risk of disease progression. Specially selected exercise programs, including low-intensity loads, allow you to reduce pain and prevent complications such as muscle atrophy and limited joint mobility. Conclusions. Thus, effective rehabilitation of middle-aged individuals with coxarthrosis requires a deep understanding of the specifics of the disorders, individual characteristics of patients, and the use of innovative techniques to ensure full restoration of physical and emotional health.
Keywords: hip joint; physical therapy; functional status; range of motion